Dataset for the publication Photo Privacy Conflicts in Social Media - A Large-Scale Empirical Study - Joel Porter, Lancaster University; Sören Preibusch, Google; Adam Joinson, University of Bath (King's College London, 2017)
This is the anonymised dataset for the publication: J. M. Such, J. Porter, S. Preibusch, A. Joinson. Photo Privacy Conflicts in Social Media: A Large-Scale Empirical Study. Accepted in ACM Conference on Human Factors in Computing Systems CHI, 2017. The Dataset contains over 1,000 multiparty privacy conflicts over co-owned photos in social media. For further details about the project, data, methods and procedures, please see the above paper. Please cite the paper if you use the dataset.
Keywords: Privacy; co-owned data; Social Media; Online Social Networks; Multiparty privacy; Group privacy; Networked privacy; Conflicts